Corporate R&D and firm efficiency: evidence from Europe's top R&D investors - Subal C. Kumbhakar; Raquel Ortega-Argilés; Lesley Potters; Marco Vivarelli; Peter Voigt (Institute for the Study of Labor (IZA), 2009)
The main objective of this study is to investigate the impact of corporate R&D activities on firms' performance, measured by labour productivity. To this end, the stochastic frontier technique is applied, basing the analysis on a unique unbalanced longitudinal dataset consisting of 532 top European R&D investors over the period 2000-2005. R&D stocks are considered as pivotal input in order to control for their particular contribution to firm-level efficiency. Conceptually, the study quantifies the technical inefficiency of a given company and tests empirically whether R&D activities could explain the distance from the efficient boundary of the production possibility set, i.e. the production frontier. From a policy perspective, the results of this study suggest that - if the aim is to leverage companies' productivity - emphasis should be put on supporting corporate R&D in high-tech sectors and, to some extent, in medium-tech sectors. By contrast, supporting corporate R&D in the low-tech sector turns out to have a minor effect. Instead, encouraging investment in fixed assets appears vital for the productivity of low-tech industries. However, with regard to firms' technical efficiency, R&D matters for all industries (unlike capital intensity). Hence, the allocation of support for corporate R&D seems to be as important as its overall increase and an 'erga omnes' approach across all sectors appears inappropriate.
Keywords: L2; O3; 330; Corporate R&D; productivity; technical efficiency; stochastic frontier analysis; Industrielle Forschung; Unternehmensentwicklung; Arbeitsproduktivität; Technische Effizienz; Schätzung; Europa